Construction of Mortality Table for Credit Life Insurance using Whittaker-Henderson Graduation Method - Prasetyo, Fajar Eko; Kwon, Hyuk-Sung (JTAM (Jurnal Teori dan Aplikasi Matematika), 2025)
Indonesian Mortality Table III (2011) and Indonesian Mortality Table IV (2019) are still used as a reference for determining life insurance premiums, one of which is determining Credit Life Insurance premium rates. With different and more specific population and risk characteristics, it is necessary to have Mortality Table that reflects the characteristics of the Credit Life Insurance. This study is a quantitative applied study that aims to construct a specialized mortality table reflecting the unique characteristics of Credit Life insurance. First, the crude mortality rates were calculated using Microsoft Excel based on Credit Life Insurance portfolio data obtained from a life insurance company having a fairly large portfolio, during the period from 2017 to 2023. The crude mortality results were then adjusted using a smoothing technique of Whittaker-Henderson method assisted with the R program and Microsoft Excel. After obtaining the smoothed mortality rates, an extrapolation was carried out using Gompertz model assisted with the R program and Microsoft Excel to obtain the mortality rate for ages between 75 and 100 years. The extrapolated results are subsequently compared with the Indonesia Mortality Table III (IMT-III) and Indonesia Mortality Table IV (IMT-IV) to assess the consistency of mortality patterns. The main contribution of this study is the development of a more representative mortality table based on empirical data from credit life insurance portfolios, an area that has not been extensively explored. The findings of this study are expected to improve the accuracy of premium pricing, technical reserve estimation, and risk management for life insurance companies offering credit life insurance products.